The influence of crosslinking temperature on the spectroscopic, thermal, and mechanical properties of poly(vinyl alcohol)/zeolite composites - Denktas, Cenk (Tubitak Scientific & Technological Research Council Turkey, 2019)
The aim of this study was to understand the effect of crosslinking temperature on the spectroscopic, thermal, and mechanical properties of poly(vinyl alcohol) (PVA)/zeolite composites. The PVA nanocomposite films were prepared using the solvent casting method with tartaric acid as the crosslinker. The changes in the structures of pure PVA film and powder clinoptilolite (CL) and nanocomposite films were analyzed by means of ATR-FTIR spectroscopy. The effect of both crosslinking temperature and CL on the composite films prepared by the addition of constant CL to the polymer matrix at different crosslinking temperatures (series II) and pure PVA films prepared with different crosslinking temperatures (series III films) shows that the tensile strengths increase with increasing crosslinking temperature, while the elongation at break of films decreases due to the crosslinking temperature and CL. The differential scanning calorimetry results show that the crosslinking temperature leads to an increase in the glass transition (T-g) of nanocomposites. According to the results of this study, both zeolite and crosslinking temperature affect the thermal and mechanical properties of the material. These results may be used for membrane technology.
Keywords: Poly(vinyl alcohol); crosslinking temperature; differential scanning calorimetry; mechanical properties; microstructure; POLYVINYL-ALCOHOL; PERVAPORATION; MEMBRANES; WATER; DEHYDRATION; ISOPROPANOL; ZEOLITES; MIXTURES; Physics